Implementation of the Fuzzy Time Series Method for Forecasting Silver Jewellery Sales - Komang Kurniawan Widiartha; Gede Dana Pramitha; Kadek Ryan Saputra Galiharta (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
Art shop Onno Silver is one of the art shops located on Jalan Raya Celuk No. 27, Celuk, Sukawati District, Gianyar, selling various types of silver jewelry such as earrings, bracelets, necklaces, rings and other types. Art shop Onno Silver only sees sales data from previous months without any more accurate calculations in sales forecasting. Art shop Onno Silver faces challenges in planning sales strategies and predicting sales in the following month due to unpredictability and high sales fluctuations, due to each category having different sales patterns that are influenced by various factors. This sales forecasting research uses the Fuzzy Time Series method. The results of this research method show the accuracy level of the earrings category MSE results of 8032.48, MAE results of 72.24, and MAPE results of 34.78%. The accuracy results for the bracelet category show MSE results of 539.37, MAE results of 20.82, and MAPE results of 26.61%. And the ring category evaluation results show MSE results of 12567.78, MAE results of 87.60, and MAPE results of 36.19%. From the evaluation results of the earrings, bracelets, and rings categories where it is in the range of 20% ? x < 50% that the forecasting accuracy is quite good. While the evaluation results of the necklace category show the MSE result of 87.43, the MAE result of 6.51, and the MAPE result of 12.35% where it is in the range of 10% ? x < 20% that the forecasting accuracy is good.